ANTIMICROBIAL ACTIVITY OF ALKALOIDS EXTRACTED FROM ADHATODA VASICA - SAWANT C.S.; SAVE S.S.; BHAGWAT A.M. (International Journal of Pharma and Bio Sciences, 2013)
Adhatoda vasica, a popular Indian medicinal plant known locally as Adulsa in Maharashatra has been explored for various biological activities. The present paper gives an account of the antimicrobial activity of alcoholic extracts and alkaloids extracted from this plant which have not been studied extensively. The hot and cold Methanolic extracts of Adhatoda vasica and alkaloids isolated from the hot methanolic extract, were evaluated for antimicrobial activity against clinically important bacteria such as Staphylococcus aureus ATCC 25923, Staphylococcus aureus NTCC 3750, Escherechia coli ATCC 25922, Proteus mirabilis, a Clinical isolate, Salmonella typhi NTCC 786, Pseudomonas aeruginosa ATCC 27853, Candida albicans MTCC 183 and Cryptococcus neoformans NCIM 3542. In vitro antimicrobial activity was performed using agar cup diffusion method. Both the (hot and cold) methanolic extracts of Adhatoda vasica were found to be active only against S. aureus and P. aeruginosa, but alkaloids isolated from these extracts` exhibited excellent antimicrobial activity against organisms investigated.